MANAJEMEN PARKIR UNTUK PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) DI DINAS PERHUBUNGAN KOTA SEMARANG - Hilda Happy Ekaryn; Augustin Rina Herawati; Dyah Hariani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
The receipt of parking retributions, which are still not constant and rather low when compared to the Semarang city's potential, demonstrates that parking regulation in the city of Semarang has not yet been implemented successfully. In terms of parking management, there are still inherent challenges including unauthorized parking and unreasonable fees. Thus, effective parking management will create a large number of parking retribution receipts, which will subsequently be used to increase Semarang City's local own-source revenue (PAD). The purpose of this research is to analyze the Semarang City Transportation Department's parking management in order to increase local own-source revenue (PAD), as well as to identify the challenges that Semarang City has in implementing parking management. In order to solve the problems and research objectives, the researcher applied George R. Terry's (2006: 342) theory of managerial functions such as planning, organizing, moving, and supervising. This research used a qualitative technique with a descriptive approach in order to provide more thorough information; furthermore, the data in this research were acquired from primary and secondary sources via interviews, observations, and literature documents. According to the findings of this research, parking management has completed all stages. The planning step is performed properly, with the transportation department planning the goals or targets to be achieved as well as the programs. Moreover, the organizing step was well-executed, with the department arranging the structure by developing a special division that managed the parking sector and assigned roles to each employee. The moving stage is already operational, however, it is not optimal. Movements in instructional programs to socialize the regulations applied, and information activities on parking spaces that can be used as parking spots, are still not ideal. Meanwhile, there has been an increase in the number of parking retribution operations, the creation of contractual arrangements or agreements, the contribution to supporting facilities, and the compiling and presenting reports. The final stage is the supervising stage. At this stage, supervision is still not operating at optimum performance. The Department of Transportation conducts two forms of supervision: direct and indirect supervision. Direct supervision is provided through monitoring directly in the field. Yet, indirect supervision is based only on income reports. However, in order to increase local own-source revenue (PAD), there are challenges in parking management in Semarang City, such as a shortage of workers at the Semarang City Transportation Department, a lack of public awareness, and many violations identified.